2003
DOI: 10.1590/s0074-02762003000100004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features of rotavirus infection in Goiânia, Goiás, Brazil, from 1986 to 2000

Abstract: Key words: rotavirus -gastroenteritis -epidemiology -seasonality - Goiás -Brazil Diarrhoea is an important cause of morbidity in humans throughout the world, affecting mainly infants and children . Group A rotavirus is the most common cause of acute gastroenteritis in young children, causing a large number of hospitalizations (Pérez-Schael et al. 1999). Rotavirus is also associated with child mortality in several countries (Bern et al. 1992, Argüelles et al. 2000, Kapikian et al. 2001. This virus was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
22
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 19 publications
7
22
2
3
Order By: Relevance
“…Therefore, the seasonality of astrovirus infection in our study could be associated with the increase of the relative air humidity resulting from heavier rainfalls in the region. These results agree with those from a previous study (Cardoso et al 2002) and differ from the pattern of rotavirus occurrence in Goiânia city, which is more prominent during the dry months (April to August) (Cardoso et al 2003, Costa et al 2004.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the seasonality of astrovirus infection in our study could be associated with the increase of the relative air humidity resulting from heavier rainfalls in the region. These results agree with those from a previous study (Cardoso et al 2002) and differ from the pattern of rotavirus occurrence in Goiânia city, which is more prominent during the dry months (April to August) (Cardoso et al 2003, Costa et al 2004.…”
Section: Discussionsupporting
confidence: 90%
“…In the Central-West Region of the country, the four seasons of the year are not well defined and only a dry and a rainy period are observed, corresponding to the months of April-August and September-March, respectively. Notably, RVAs are mainly detected during the dry season (Cardoso et al 2003, Costa et al 2004, whereas astroviruses and caliciviruses are more prevalent in the rainy period (Borges et al 2006. However, in the present investigation, a seasonal pattern of circulation was not observed for HBoV-1, which was detected throughout the year during the study period.…”
Section: Discussioncontrasting
confidence: 58%
“…Based on the mean occurrence of other gastroenteric viruses in the region, HBoV-1 could be considered the third most common after RVAs and human cali-civiruses (Cardoso et al 2003, Costa et al 2004, Borges et al 2006, Andreasi et al 2008. Additionally, it must be noted that primer pairs that detect only HBoV species 1 and 3 were used in this study and if one considers that species 2 appears to be predominant in individuals with gastroenteritis (Arthur et al 2009, Chow et al 2010, the observed positivity rate for HBoVs may be underestimated.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations